Glucose Biochip Based on Flexible Carbon Fiber Electrodes: In Vivo Diabetes Evaluation in Rats. Issue 4 (9th January 2015) - Iost, Rodrigo M.; Sales, Fernanda C. P. F.; Martins, Marccus V. A.; Almeida, Maria C.; Crespilho, Frank N.
Abstract This paper reports an implantable biochip for intravenous glucose monitoring in rat blood. A key feature of this device is the combination of the flexibility of the flexible carbon fiber (FCF) electrodes for the micromanipulation of the biosensor in the implant. FCF, modified with a neutral red electrochemical mediator and an enzyme glucose oxidase, enables the biochip to be manipulated conveniently during insertion in the rat veins. For in vivo experiments, the biochip is inserted into the jugular vein of a living rat (Rattus novergicus) using a poly(propylene) catheter. The capability for in vivo glucose detection is evaluated with a normal concentration of glucose (30 mg dL−1) and with a diabetic simulation (200 mg dL−1). Through electrochemical data, this type of biochip can distinguish different concentration of glucose in the blood of the animal. The biochip showed promise performance for future applications of implantable bioelectronics devices.